2016
DOI: 10.1177/1049731516666328
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ Satisfaction With Family Involvement Meetings

Abstract: Bivariate and logistics regression analyses were conducted to examine the effectiveness of child welfare agencies' Family Group Decision-Making (FGDM) practices focused on strengthening families and positive outcomes for children. This study evaluates one mid-Atlantic state's implementation of a FGDM called family involvement meetings (FIMs) to improve family strengths and their active engagement in the service planning process. Methods: Through use of a FIM Feedback Survey, participants provided satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…To facilitate shared resources and responsibilities, an essential step is to respect the culture of the family, acknowledge family strengths, and involve family members in the decision-making process. Emerging research has shown that implementing family-centered practice increases family’s satisfaction with services (Ahn et al, 2018), helps fulfill children and families’ short-term goals (Xu et al, 2017), and prevents child maltreatment (DePanfilis & Dubowitz, 2005). Although family-centered practice has been widely implemented in the United States, there is a lack of valid and reliable measures to capture child welfare workers’ family-centered practices.…”
mentioning
confidence: 99%
“…To facilitate shared resources and responsibilities, an essential step is to respect the culture of the family, acknowledge family strengths, and involve family members in the decision-making process. Emerging research has shown that implementing family-centered practice increases family’s satisfaction with services (Ahn et al, 2018), helps fulfill children and families’ short-term goals (Xu et al, 2017), and prevents child maltreatment (DePanfilis & Dubowitz, 2005). Although family-centered practice has been widely implemented in the United States, there is a lack of valid and reliable measures to capture child welfare workers’ family-centered practices.…”
mentioning
confidence: 99%